Analisis Reaksi Pasar Terhadap Pengumuman Dividen Saham - Pastika, I Wayan Arya; Widanaputra, A. A. G. P. (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p30, 2019)
The purpose of this study was to determine the effect of stock dividend announcement on abnormal return before and after stock dividend announcement. The research period was used from 2010-2018. This study using event study approach. Population in this study used all companies that listed on Indonesia Stock Exchange. The sample was selected by using purposive sampling technique and obtained 23 companies that made stock dividend announcement during 2010-2018. Estimated return was determine using market adjusted model. The parametric analysis test in this study used a paired sample t-test. This research result can be concluded that stock dividend announcement does not affect the abnormal return, shown by the result of paired sample t-test with level of significant 0,455 (0,455>0,05) which means that there is no significant difference in abnormal return between before and after stock dividend announcement. Keyword s: Dividend stock, abnormal return, market reaction.